Five Irish women : The second republic, 1960-2016 - Nolan, Emer, 1966- (Book collections on Project MUSE., 2019)
Five Irish Women is comprised of five interlinked portraits of exceptional Irish women from various fields - literature, journalism, music, politics - who have achieved outstanding reputations since the 1960s: Edna O'Brien, Sinead 'Connor, Nuala O'Faolain, Bernadette McAliskey and Anne Enright. Several of these could claim to be among the best-known Irish people of their day. The book looks at their achievements -- works of art in some cases, but also life-writing, interviews and speeches - and at their reception in Ireland and elsewhere, shedding light on some of their shared preoccupations, including equality, sexuality and nationalism. The main focus is on the ways in which these distinguished women make sense of their formative experiences as Irish people and how they in turn have been understood as representative figures in modern Ireland.